2001
DOI: 10.1038/sj.jhh.1001150
|View full text |Cite
|
Sign up to set email alerts
|

The Haemodynamic Instability Score (HIS) for assessment of cardiovascular reactivity in hypertensive and normotensive patients

Abstract: The normal response to postural challenge is characterised by maintenance of relatively stable blood pressure (BP) and heart rate (HR) after 30 sec to 30 min of headup tilt. The objective of the present study was to determine the degree of instability of cardiovascular responses to postural challenge in normotensive and hypertensive subjects. In the initial phase of the study, two groups of age and sex-matched subjects were assessed: essential hypertension (n ‫؍‬ 20) and healthy (n ‫؍‬ 37). The BP and HR were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In our results, the FD provided three out of five independent predictors that characterized the CFS group. Thus, the importance of fractal analysis in the characterization of the cardiovascular reactivity was substantiated and results of previous studies, which utilized a different technique [11,12,24,25], were confirmed.…”
Section: Discussionmentioning
confidence: 76%
“…In our results, the FD provided three out of five independent predictors that characterized the CFS group. Thus, the importance of fractal analysis in the characterization of the cardiovascular reactivity was substantiated and results of previous studies, which utilized a different technique [11,12,24,25], were confirmed.…”
Section: Discussionmentioning
confidence: 76%
“…In the CARDIA study including 2,781 young adults to assess the relationship between positional BP change and incidence of hypertension over a follow-up period of 8 years, there was a significantly increased risk of developing hypertension in OHT persons [4]. The cardiovascular reactivity to orthostatic stress has been used to devise a hemodynamic instability score which has been shown to be associated with the development of hypertension [25]. Potentially, detection of OHT might help to identify a subset of pre-hypertensive patients that might have progression of their hypertension and develop hypertensive target organ damage (table 2).…”
Section: The Clinical Spectrum Of Ohtmentioning
confidence: 99%
“…[28][29][30] The HIS identified a distinctive cardiovascular reactivity in patients with essential hypertension. 7 Thus, the correlation of results obtained by both the FRAS and the HIS methods supports the authenticity of reactivity phenotypes.…”
Section: Distinct Cardiovascular Reactivity Patternsmentioning
confidence: 51%
“…These include fractal analysis, 6,7 recurrence quantification analysis, 8,9 and multivariate models that consider the relation between two or more cardiovascular signals. 10 It has been suggested that joint quantification of BP and HR fluctuations, and utilization of non-Euclidean mathematic analysis may provide more reliable information on cardiovascular reactivity.…”
Section: Introductionmentioning
confidence: 99%